Energy Method for Identification of Electromechanical Devices and Systems - D. I. Rodkin; Y. V. Romashihin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper considers a method for determination of induction motor electromagnetic parameters while using complete instant power equations. The methods for AC motor electromagnetic parameters are proposed in the paper. The paper reveals the method efficiency while determining induction motor electromagnetic parameters.